Prosodic skills of Spanish‐speaking children with developmental language disorder. Issue 4 (18th May 2021) - Calet, Nuria; Martín‐Peregrina, Manuel Ángel; Jiménez‐Fernández, Gracia; Martínez‐Castilla, Pastora
Abstract: Background: Phonological difficulties in children with developmental language disorder (DLD) are well documented. However, abilities regarding prosody, the rhythmic and melodic characteristics of language, have been less widely studied, particularly in Spanish. Moreover, the scant research findings that have been reported are contradictory. These considerations justify our new research into the question, focusing on Spanish‐speaking children with DLD. Aims: To examine a wide range of prosodic skills among Spanish‐speaking children with DLD. To analyse the relationships between prosody and other language measurements. Methods & Procedures: Prosodic skills were assessed through the Spanish version of the Profiling Elements of Prosody in Speech‐Communication (PEPS‐C) battery. The performance of 19 children aged 5–11 years with DLD was compared with that of a chronological age‐matched control group of 19 typically developing children. Language skills were also assessed. Outcomes & Results: There were significant differences between the group with DLD and the control group in terms of skills involving prosody functions and forms: turn‐end and chunking signalling, contrastive focus and affect expression and understanding, discriminating and the imitation of prosodic patterns in both words and phrases. Conclusions & Implications: Spanish‐speaking children with DLD present impairments not only when prosody interacts with language but also in the processing of prosody alone. The study results suggest that prosody is related to lexicon and grammar in children with DLD. The prosodic impairments of Spanish‐speaking children with DLD could produce a negative impact on their language functioning and could also relate to their emotional and social difficulties. Consideration should therefore be given to focusing future interventions on prosodic skills in Spanish‐speaking children with DLD. What this paper adds: What is already known on the subject: Although deficits in segmental phonology have been extensively studied in DLD, relatively little research has been conducted into supra‐segmental phonology, especially among speakers of Spanish. To our knowledge, only one previous study has analysed the prosodic skills of Spanish‐speaking children with DLD, and this only focused on prosody while reading. No analysis was made of the use of prosody in language comprehension and expression. What this study adds to existing knowledge: This is the first study to analyse competence in a wide range of prosodic skills among Spanish‐speaking children with DLD by using the PEPS‐C battery. Spanish‐speaking children with DLD present impairments in prosody functions and forms, which are related to other language skills. What are the potential or actual clinical implications of this work?: Prosodic impairments among Spanish‐speaking children with DLD could contribute to explaining both their language difficulties and their socio‐emotional problems. The results obtained suggest that Spanish‐speaking children with DLD could benefit from interventions focused on prosody.